2014
DOI: 10.4269/ajtmh.13-0382
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Permeability and Adherens Junction Disruption Induced by Junín Virus Infection

Abstract: Abstract. Junín virus (JUNV) is endemic to the fertile Pampas of Argentina, maintained in nature by the rodent host Calomys musculinus, and the causative agent of Argentine hemorrhagic fever (AHF), which is characterized by vascular dysfunction and fluid distribution abnormalities. Clinical as well as experimental studies implicate involvement of the endothelium in the pathogenesis of AHF, although little is known of its role. JUNV has been shown to result in productive infection of endothelial cells (ECs) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…muridarum infection. These results imply that TLR3-deficiency leads to a more acute breakdown in the integrity cellular tight junctions (TJs) and/or adherence junctions (AJs) that are known to be affected during cellular invasion by specific viral and bacterial pathogens [34, 36, 37, 4042]. To ascertain whether the dissimilarity in macromolecular permeability and TER between the wild-type and TLR3-deficient OE cells correlates with a differential regulation in TJ gene expression during Chlamydia infection, we measured gene transcription levels of the candidate TJ proteins by quantitative real-time-PCR (qPCR).…”
Section: Resultsmentioning
confidence: 99%
“…muridarum infection. These results imply that TLR3-deficiency leads to a more acute breakdown in the integrity cellular tight junctions (TJs) and/or adherence junctions (AJs) that are known to be affected during cellular invasion by specific viral and bacterial pathogens [34, 36, 37, 4042]. To ascertain whether the dissimilarity in macromolecular permeability and TER between the wild-type and TLR3-deficient OE cells correlates with a differential regulation in TJ gene expression during Chlamydia infection, we measured gene transcription levels of the candidate TJ proteins by quantitative real-time-PCR (qPCR).…”
Section: Resultsmentioning
confidence: 99%
“…The junction proteins are essential to regulating the integrity of the endothelial monolayer and playing a dominant role in the stability of endothelial cell contacts. The disruption of junction proteins occurs in the early-stage of vascular enhanced endothelial permeability [ 35 ], which represents one of the initial pathologic processes leading to endothelial dysfunction. In the present study, our data demonstrate that the protein expressions of ZO-1 and VE-Cadherin in RAECs were significantly reduced under high glucose, whereas such decreases were significantly attenuated in simvastatin treatment through NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, JEV also induces microglial activation in the brain (Ghoshal et al, 2007), leading to expression of numerous immune-related proteins such as chemokines methyl-accepting chemotaxis protein (MCP-1), macrophage inflammatory protein 1 (MIP-1α, MIP-1β), RANTES), cytokines (IL-1, IL-6, IL-18, TNF-α), vascular endothelial growth factor (VEGF), lymphotoxin, and multiple matrix metalloproteinases (MMPs) (Banati et al, 1993;Shima et al, 1995;Ubogu et al, 2006). It has been confirmed that high levels of IL-6 and MCP-1 after virus infection led to increased vascular permeability (Lander et al, 2014). Moreover, deformation of TJs and disruption of the BBB due to high levels of IL-6 have been detected in a mouse model of JE (Gupta and Rao, 2011;Yang et al, 2011).…”
Section: Disruption Of Tight Junctions Via Icam-1 and Cinc-1mentioning
confidence: 99%